1999
DOI: 10.1046/j.1471-4159.1999.721773.x
|View full text |Cite
|
Sign up to set email alerts
|

Brain Neurotransmitter Deficits in Mice Transgenic for the Huntington’s Disease Mutation

Abstract: Huntington's disease (HD) is associated with an expansion in the CAG repeat sequence of a gene on chromosome 4, resulting in a neurodegenerative process particularly affecting the striatum and with profound but selective changes in content of various neurotransmitters. Recently, transgenic mice expressing a fragment of the human HD gene containing a large CAG expansion have been generated; these mice exhibit a progressive neurological phenotype that includes motor disturbances, as well as neuronal deficits. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
70
3

Year Published

2000
2000
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(86 citation statements)
references
References 24 publications
13
70
3
Order By: Relevance
“…These findings are in agreement with the results obtained when R6/1 and R6/2 lines were compared. Whereas no differences in dopamine content are detected in R6/1 mice (Petersen et al 2002;present results), studies performed in homogenates of R6/2 mouse striata, in which BDNF is decreased (Zhang et al 2003), demonstrated diminished levels of dopamine (Reynolds et al 1999;Hickey et al 2002). In addition, dopamine concentration in post-mortem striatal HD tissue has been shown to be decreased (Kish et al 1987), a finding that can also be related to the reduced levels of BDNF (Ferrer et al 2000).…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…These findings are in agreement with the results obtained when R6/1 and R6/2 lines were compared. Whereas no differences in dopamine content are detected in R6/1 mice (Petersen et al 2002;present results), studies performed in homogenates of R6/2 mouse striata, in which BDNF is decreased (Zhang et al 2003), demonstrated diminished levels of dopamine (Reynolds et al 1999;Hickey et al 2002). In addition, dopamine concentration in post-mortem striatal HD tissue has been shown to be decreased (Kish et al 1987), a finding that can also be related to the reduced levels of BDNF (Ferrer et al 2000).…”
Section: Discussionmentioning
confidence: 77%
“…However, dopaminergic deficits are more apparent in the R6/2 line (Bibb et al 2000;Hickey et al 2002;Petersen et al 2002), which shows a more rapid progression of HD symptoms (Mangiarini et al 1996). These dopaminergic alterations include decreased levels of D 1 and D 2 dopamine receptors (Cha et al 1998), reduced dopamine content (Reynolds et al 1999), and age-dependent impairment in the behavioural response to dopamine stimulants (Hickey et al 2002).The mechanism underlying HD pathogenesis remains to be elucidated, but it could involve the gain of toxic functions, the loss of beneficial functions of wild type (wt)-htt or both. Wt-htt increases the transcription of the brain-derived neurotrophic factor (BDNF) (Zuccato et al 2001), a neuroprotective factor for striatal (Bemelmans et al 1999;Perez-Navarro et al 1999Kells et al 2004) and dopaminergic neurons (Hyman et al 1991).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A reduction of dopamine metabolites was also observed in human SCA3 cases (Higgins et al, 1996), as well as in transgenic mouse models of HD (Reynolds et al, 1999;Duan et al, 2004) and HD patients (Reynolds and Garrett, 1986). Interestingly, normalization of observed serotonin deficits in HD mice delayed neurodegeneration (Reynolds et al, 1999;Duan et al, 2004).…”
Section: Discussionmentioning
confidence: 81%
“…It has been reported that levels of serotonin and BDNF are decreased in HD mice (Reynolds et al, 1999, Zuccato et al, 2001) and HD patients (Ferrer et al, 2000;. There is a reciprocal interaction between BDNF and serotonergic signaling, in which BDNF enhances serotonin production and release, while serotonin stimulates BDNF production .…”
Section: Discussionmentioning
confidence: 99%